Rewarding consumers for recycling packaging : Kimberly-Clark seeks shared value - Beckman, Sara Lynn, (SAGE Knowledge. Cases., 2017)
This case describes how Kimberly-Clark is working to encourage consumer recycling of flexible plastic film packaging, which is wrapped around many of its products, including paper towels, toilet paper, and more. An infrastructure already exists for consumers to return this film to retail stores for recycling, but estimated return rates remain low. Furthermore, Kimberly-Clark is not directly involved in the recycling transaction; retail stores collect the packaging and sell it to recycling companies. Kimberly-Clark is considering developing a consumer rewards program to incentivize store return of the packaging. Funding such a program will likely require Kimberly-Clark to identify new sources of value throughout the film-packaging lifecycle.